Poly(oligonucleotide) - James, Carrie R. (American Chemical Society, 2014)
[Image: see text] Here we report the preparation of poly(oligonucleotide) brush polymers and amphiphilic brush copolymers from nucleic acid monomers via graft-through polymerization. We describe the polymerization of PNA-norbornyl monomers to yield poly-PNA (poly(peptide nucleic acid)) via ring-opening metathesis polymerization (ROMP) with the initiator, (IMesH(2))(C(5)H(5)N)(2)(Cl)(2)RuCHPh.1 In addition, we present the preparation of poly-PNA nanoparticles from amphiphilic block copolymers and describe their hybridization to a complementary single-stranded DNA (ssDNA) oligonucleotide.